Music as a window into real-world communication - Izen, Sarah C.; Cassano-Coleman, Riesa Y.; Piazza, Elise A. (Frontiers in Psychology, 2023)
Communication has been studied extensively in the context of speech and language. While speech is tremendously effective at transferring ideas between people, music is another communicative mode that has a unique power to bring people together and transmit a rich tapestry of emotions, through joint music-making and listening in a variety of everyday contexts. Research has begun to examine the behavioral and neural correlates of the joint action required for successful musical interactions, but it has yet to fully account for the rich, dynamic, multimodal nature of musical communication. We review the current literature in this area and propose that naturalistic musical paradigms will open up new ways to study communication more broadly.